30-day Mortality Following Revision of Hip Arthroplasty, A Cohort Study Based on the Swedish Perioperative Registry 2017-2022 - Arvid Ekeberg; Johanna Albert; Olof Sköldenberg; Jon Karlsson; Jan G. Jakobsson (Geriatric Orthopaedic Surgery & Rehabilitation)
Introduction In Sweden approximately 9% of hip-arthroplasty require a revision. All-cause 30-day mortality following hip revisions in Sweden is unknown. Aim To assess all-cause 30-days mortality among hip-revision in Sweden and whether mortality has changed 2017-2022 based on data from the Swedish perioperative register (SPOR) adjusted for sex, age, ASA-class, indication and fixation technique. Method This observational cohort study includes all hip revisions registered in SPOR between 2017 – June 2022 analysing 30-day postoperative mortality rates. Inclusion criteria: age >18 having had a hip arthroplasty revision ICD-10-SE codes NFC. Binary-logistic-regressions estimated odds-ratio (OR) for 30-days mortality over the study period, adjusted for sex, age, ASA-class, indication and fixation technique. Result 6937 patients were included in the analysis, 3333 females and 3063 males mean-age 73 years with an overall 30-day mortality rate of 1.3%. No significant differences in 30-day mortality were found over the study-period. There was no death within 30-days among patients below 65 years and within ASA-class I. Males had a mortality rate of 1.4% vs females 1.1% (ns.). Adjusted OR was significantly higher for patients with age >80 years OR 9.1 ( P < 0.001), AS-classes III OR 3.9 and IV 14.9 ( P < 0.001) infection 3.4 and fracture 9.1 ( P < 0.001) but fixation technique had not. Conclusion The all-cause 30-day mortality in Sweden was 1.3% with minor differences over the study period and between sexes, while high age especially above 80 and ASA-classes III and IV significantly increased the adjusted OR for 30-day mortality. Efforts to further optimize the perioperative care of this patient group are of importance.